Introduction to sociological theory theorists, concepts, and their applicability to the twenty-first century - Dillon, Michele,1960 (Wiley Blackwell, 2014)
The extensively revised and updated second edition combines carefully chosen primary quotes with wide-ranging discussion and everyday illustrative examples to provide an in-depth introduction to classical and contemporary sociological theory.Combines classical and contemporary theory in a single, integrated text. Short biographies and historical timelines of significant events provide context to theorists' ideas. Innovatively builds on excerpts from original theoretical writings with detailed discussion of the concepts and ideas under review.